Complementary foliar fertilization improves the yield, health and profitability of cocoa in rainfed agroecosystems (2022)
Foliar fertilization allows supplementing crop nutrition under limiting soil and climate conditions. The aim of the research was to evaluate the effectiveness of complementary foliar nutrition on the yield, health and profitability of national cocoa under rainfed conditions. The treatments evaluated were foliar fertilization with NPK (T1), macro and micronutrients + diatomaceous earth (T2), macro and micronutrients + phytoregulators + diatomaceous earth (T3), macro and micronutrients + phytoregulators + amino acids + diatomaceous earth (T4), NPK soil fertilization (T5) and control treatment (T6). A randomized complete block design was used, with four replicates and 24 experimental units. The main variables recorded were incidence of diseased ears (IDE), dry grain yield (DGY) and net economic benefit (NEB). Data were analyzed with ANOVA and Tukey's test of means (α = 0.05). The results indicated significant statistical differences (p<0.05) for the IDE and the DGY. The T4 treatment reached the lowest IDE with 40.87%, in relation to the control treatment that showed an IDE of 65.02%.Similarly, treatment T4 achieved the highest DGY with 1395 kg ha-1, which represented an increase of 13.41, 20.28, 35.85, 41.37 and 57.39%, compared to treatments T3, T2, T1, T5 and T6, respectively. The T4 treatment also achieved the highest NEB with 802 USD ha-1, compared to the rest of the treatments evaluated. It is concluded that complementary foliar fertilization is economically viable for national cocoa in rainfed agroecosystems.